Parthanatos drives cognitive decline in repeated brain trauma: MSC-derived exosomes as a novel therapeutic strategy - Refat M. Selim, Heba Mohammed; El-Gazar, Amira A.; Abdallah, Dalaal M.; Abo-Zalam, Hagar B.; Ragab, Ghada M.; Abdallah, Ahmed N.; El-Gazar, Rabab A.; Alshehri, Sultan; Yousef, Einas M.; Ballal, Rayan; Aljarallah, Sahar N.; Saleh, Asmaa; et al. (Frontiers in Pharmacology, 2025)
IntroductionRepetitive traumatic brain injury (RTBI) represents a cumulative neurological insult associated with progressive neurodegeneration and limited therapeutic options. In this study, we uniquely evaluate the neuroprotective potential of mesenchymal stem cell (MSC)-derived exosomes in a rat model of RTBI, an area scarcely explored.MethodsRTBI was induced via a controlled mechanical impact to the skull once every day for 5 days. MSC-derived exosomes were administered 24 h after the final insult in two paradigms: a single dose (MSC-Ex1) with 2 weeks of follow-up, and a dual dose (MSC-Ex2) given 1 week apart, with sacrifice 1 week later. Rats were assigned to four groups: control, RTBI, RTBI + MSC-Ex1, and RTBI + MSC-Ex2.ResultsMSC-derived exosome regimens comparably restored cognitive performance in the Novel Object Recognition and Y-maze tests. While both treatment paradigms preserved cortical histoarchitecture, the double-dose regimen led to a more pronounced restoration compared to the moderate tissue recovery observed in the single-dose group. Crucially, this work identifies parthanatos inhibition as a novel mechanistic axis for MSC-derived exosomes-mediated neuroprotection. MSC-derived exosomes attenuated excitotoxicity and oxidative stress, quelling the parthanatos cascade by suppressing PARP1, PAR polymers, nuclear AIF and MIF, as well as calpain, key executors of this caspase-independent cell death pathway. Additionally, MSC-derived exosomes normalized cyclophilin B and Hsp70 levels, suggesting their compensatory role in modulating the endogenous stress response.ConclusionOverall, these findings demonstrate that MSC-derived exosomes counteract RTBI-induced neurodegeneration through multifaceted mechanisms, with parthanatos suppression at the core. Importantly, the dual-dosing regimen conferred no significant benefit over the single dose, highlighting the therapeutic promise of early intervention. This study positions MSC-derived exosomes as a novel, cell-free therapy capable of intercepting RTBI-induced neuropathology by targeting an under recognized form of programmed cell death.